Selection of timing of continuous renal replacement therapy in patients with acute kidney injury: A meta-analysis of randomized controlled trials - Jiawei Qi; Wenwen Wu; Jingzhu Wang; Xin Guo; Chengyun Xia (PLoS ONE, 2025)
Acute kidney injury (AKI) is associated with high death rates and unfavorable outcomes. Previous studies evaluating the effect of the timing of CRRT therapy on the prognosis of patients with AKI have shown inconsistent results. Consequently, we aimed to assess the impact of continuous renal replacement therapy (CRRT) initiation on the outcomes of patients with AKI. This meta-analysis identified eligible randomized controlled trials (RCTs) via comprehensive searches of PubMed, Embase, and the Cochrane databases from their creation until June 1, 2024. Outcomes, including 28-, 60-, and 90-day mortality and adverse event incidence, were compared between the early and delayed CRRT groups post-randomization. Twelve RCTs (n = 1,244) were included. Meta-analysis indicated that early initiation of CRRT did not significantly affect 28-day mortality (RR 0.91 [0.79, 1.06]; p =  0.23; I2 =  0). Early CRRT initiation correlated with a shorter length of ICU stay [MD -3.24 (-5.14, -1.35); p = 0.0008; I2 = 36%] but did not significantly affect hospital stay duration [MD -7.00 (-14.60, 0.60); p = 0.07; I2 = 38%]. The early initiation of CRRT was associated with a significant reduction in RRT dependency at discharge [RR 0.57 (0.32, 0.99); P = 0.05; I2 = 0%; P = 0.47]. Compared to delayed CRRT, early CRRT was associated with higher incidence rates of hypotension [RR 1.26 (1.06, 1.50); p = 0.008; I2 = 0%], thrombocytopenia [RR 1.53 (1.11, 2.10); p = 0.009; I2 = 0%], and hypophosphatemia [RR 3.35 (2.18, 5.15); p < 0.00001; I2 = 11%]. Our findings suggest that although early CRRT initiation is associated with short intensive care unit stays and reduced RRT dependence, it has no significant effect on mortality and is in fact associated with higher incidence rates of hypotension, thrombocytopenia, and hypophosphatemia. Therefore, early CRRT should be used clinically with caution and consideration of potential adverse effects.